Chemical controls on fault behavior: Weakening of serpentinite sheared against quartz‐bearing rocks and its significance for fault creep in the San Andreas system. Issue 5 (28th May 2013) - Moore, Diane E.; Lockner, David A.
Abstract: [1] The serpentinized ultramafic rocks found in many plate‐tectonic settings commonly are juxtaposed against crustal rocks along faults, and the chemical contrast between the rock types potentially could influence the mechanical behavior of such faults. To investigate this possibility, we conducted triaxial experiments under hydrothermal conditions (200–350°C), shearing serpentinite gouge between forcing blocks of granite or quartzite. In an ultramafic chemical environment, the coefficient of friction, μ, of lizardite and antigorite serpentinite is 0.5–0.6, and μ increases with increasing temperature over the tested range. However, when either lizardite or antigorite serpentinite is sheared against granite or quartzite, strength is reduced to μ  ~ 0.3, with the greatest strength reductions at the highest temperatures (temperature weakening) and slowest shearing rates (velocity strengthening). The weakening is attributed to a solution‐transfer process that is promoted by the enhanced solubility of serpentine in pore fluids whose chemistry has been modified by interaction with the quartzose wall rocks. The operation of this process will promote aseismic slip (creep) along serpentinite‐bearing crustal faults at otherwise seismogenic depths. During short‐term experiments, serpentine minerals reprecipitate in low‐stress areas, whereas in longer experiments, new Mg‐rich phyllosilicates crystallize in response to metasomatic exchanges across the serpentinite‐crustal rock contact. Long‐term shear of serpentinite against crustal rocks will cause the metasomatic mineral assemblages, which may include extremely weak minerals such as saponite or talc, to play an increasingly important role in the mechanical behavior of the fault. Our results may explain the distribution of creep on faults in the San Andreas system. Key Points: Serpentinite is markedly weakened when sheared against quartz‐bearing rocks The weakening is interpreted in terms of solution‐transfer processes Our results may explain the occurrence of creep in the San Andreas System